Single‐dose of LC51‐0255, a selective S1P1 receptor modulator, showed dose‐dependent and reversible reduction of absolute lymphocyte count in humans. Issue 4 (23rd January 2022) - Won Lee, Sang; Hwang, Inyoung; Oh, Jaeseong; Lee, SeungHwan; Jang, In‐Jin; Yu, Kyung‐Sang
Abstract: Reducing the peripheral absolute lymphocyte count (ALC) is a promising therapeutic approach in treating autoimmune diseases. LC51‐0255 is a sphingosine‐1‐phosphate 1 receptor modulator, which is known to decrease the peripheral ALC. We aimed to assess the pharmacokinetics (PKs), pharmacodynamics (PDs), safety, and tolerability profiles of LC51‐0255 after a single oral administration in healthy subjects. A randomized, double‐blind, placebo‐controlled, dose‐escalation study was conducted in 50 healthy subjects. Each subject orally received LC51‐0255 (0.25, 0.5, 1, 2, or 4 mg) or its matching placebo in an 8:2 ratio. Blood and urine samples were collected to assess the PKs, and PDs was evaluated using peripheral ALC and 24‐h hourly heart rate data. Safety and tolerability were assessed by monitoring treatment emergent adverse events (TEAEs), vital signs, 12‐lead electrocardiogram (ECG), continuous 24‐h ECG (via Holter monitoring), clinical laboratory tests, ophthalmologic tests, pulmonary function tests, and physical examinations. A single dose of LC51‐0255 reduced ALC and heart rate in a reversible and dose‐dependent manner. Systemic exposure of LC51‐0255 increased dose‐dependently and its half‐life ranged from 72.2 to 134.0 h. ALC and the systemic exposure of LC51‐0255 seemed to be negatively correlated. LC51‐0255 was well‐tolerated up to 2 mg, and the most common TEAE was bradycardia. The results of this study suggest that LC51‐0255 can be developed into a beneficial treatment option for autoimmune disease.